Frequency of Poor Apgar Score Among Neonates Delivered by Women with Normal Versus Abnormal Cardiotocography (Medical Forum Monthly, 2021)
Objective: To compare frequency of poor APGAR SCORE among neonates delivered by women with normal versus abnormal cardiotocography.Study Design: Prospective cohort studyPlace and Duration of Study: This study was conducted at the Study was conducted at Gynae / Obs Unit - I, Dow University of Health Sciences, Karachi from January to June 2019 for a period of 6 months.Materials and Methods: All patients who fulfilled the inclusion criteria and visited OPD of Department of Gynae/Obs Unit - I, Dow University of Health Sciences, Karachi were included in the study. After ethical approval and informed and written consent patients were divided into two groups. Group A (exposed i.e. abnormal CTG) & B (non-exposed i.e normal CTG). Outcome was checked by comparing both the groups for APGAR score at 5 minutes.Results: Total 120 low risk pregnant patients were included. The mean age of women was 27.90+4.527 years. The mean APGAR score in group A was 5.562+1.453, while in group B the mean APGAR score was 7.083+0.577.2. Conclusion: In this study women having normal CTG has better APGAR score in their newborns as compared to abnormal CTG. CTG is a useful and indispensable adjunct to monitor the condition of endangered fetus. The number of patients having abnormal CTG in low risk pregnancies is not negligible. Abnormal CTG necessitates cesarean section. Therefore, adjunctive methods are required to improve the sensitivity and specificity of fetal monitoring if unnecessary interventions are to be avoided.